Tuition Fees as a Commitment Device - Nadine Ketel; Jona Linde; Hessel Oosterbeek; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2014)
This paper reports on a field experiment testing for sunk-cost effects in an education setting. Students signing up for extra-curricular tutorial sessions randomly received a discount on the tuition fee. The sunk-cost effect predicts that students who receive larger discounts will attend fewer tutorial sessions. For the full sample, we find little support for this hypothesis, but we find a significant effect of sunk costs on attendance for the 45% of students in our sample who are categorized as sunk-cost prone based on hypothetical survey questions. For them higher tuition fees can serve as a commitment device to attend classes.
Keywords: C93; D03; I22; 330; sunk-cost effect; higher education; field experiment